Prediction of genetic gain in Ficus variegata progeny trial based on breeding value - LILIEK HARYJANTO; Prastyono Prastyono; Yayan Hadiyan; Mudji Susanto (Society for Indonesian Biodiversity, 2019)
Abstract. Haryjanto L, Prastyono, Hadiyan Y, Susanto M. 2019. Prediction of genetic gain in Ficus variegata progeny trial based on breeding value. Biodiversitas 20: 2994-2999. Prediction of genetic gain in Ficus variegata Blume progeny trial based on breeding values. The aim of this study was to estimate the breeding value based on components variance and genetic gain prediction of Ficus variegata Blume using REML/BLUP. A total of 17 families of Ficus variegata Blume were evaluated at three years after planting at progeny trial in Mangunan, Bantul, Yogyakarta laid out in Randomized Completely Block Design (RCBD). Estimation of variance family (height and diameter) were ± 5% of total variance. Narrow-sense individual heritability was moderate (0.27 and 0.21 respectively) indicated promising genetic improvement. Strong genetic correlation of height and diameter (rG=0.9) indicated that improving a trait will improving others. BLUP analysis for diameter trait showed that the best individual value from best family selection was appropriated with restriction 10 family and 5 individual per family and genetic gain prediction was 15.83% gave acceptable rate of inbreeding 2% per generation.